1999
DOI: 10.1002/etc.5620180816
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between biological and physical availabilities of phenanthrene in soils and soil humin in aging experiments

Abstract: The bioavailability of an organic compound in a soil or sediment commonly declines with the soil‐chemical contact time (aging). A series of parallel desorption and bioavailability experiments was carried out on phenanthrene previously aged up to ∼100 d in Mount Pleasant silt loam (Mt. Pleasant, NY, USA) or Pahokee peat soil to determine as a function of the aging period the degree of correlation between the reduction in bioavailability and the rate and extent of desorption and the influence of soil organic mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…Sorption and distribution of HOCs in SOM fractions have received great attention, and many results have been presented for natural soils. Different SOM fractions showed different sorption/desorption properties, which affected the fate of HOCs in soils (Luo et al 2008;Pan et al 2006;White et al 1999). Studies have revealed that the sorption nonlinearity and hysteresis increased in the order of humic acid/ fulvic acid (HA/FA)<soil<HM (Pan et al 2006;Xing and Pignatello 1997).…”
Section: Responsible Editor: Nicole Mathersmentioning
confidence: 99%
“…Sorption and distribution of HOCs in SOM fractions have received great attention, and many results have been presented for natural soils. Different SOM fractions showed different sorption/desorption properties, which affected the fate of HOCs in soils (Luo et al 2008;Pan et al 2006;White et al 1999). Studies have revealed that the sorption nonlinearity and hysteresis increased in the order of humic acid/ fulvic acid (HA/FA)<soil<HM (Pan et al 2006;Xing and Pignatello 1997).…”
Section: Responsible Editor: Nicole Mathersmentioning
confidence: 99%
“…The amount of methanol/water extractable pyrene in soils with either low or high concentration of pyrene was low as well, but the proportion of PAHs extracted by butanol was much higher during 24-week aging time (Macleod and Semple 2003). It has been suggested that methanol/water removed nonpolar parent compounds and polar metabolites (Kelsey et al 1997) and butanol removed the weakly associated fraction of HOCs in soil (White et al 1999). In the present study, the similar amount of PAHs was also extracted by methanol/water.…”
Section: Discussionmentioning
confidence: 97%
“…This phenomenon also referred to "aging" actually encompasses multiple processes including the diffusion and sorption of PAHs into the soil organic and inorganic fractions. It highlights the fact that (bio)availability decreases with increasing contact time (Hatzinger and Alexander, 1995;White et al, 1999).…”
Section: Pahs Reactivity In Soilsmentioning
confidence: 89%
“…PAHs dissipation in soil is mostly driven by two processes: adsorption and biodegradation (White et al, 1999;Wilcke, 2000). When PAHs enter the soil, they rapidly sorb on minerals and organic matters in soil aggregates.…”
Section: Pahs Reactivity In Soilsmentioning
confidence: 99%